Complete Shotokan karate history, philosophy, and practice - Rielly, Robin L.
Complete shotokan karate is actually two books in one: a thorough history of Japanese karate in Asia and the United States, and an instructional manual for students of the Shotokan method. Part one outlines the history of karate from its probable origins in India (or perhaps Greece), and its transmission from China through Okinawa to Japan. Relevant aspects of Japanese history and culture, such as the samurai ethos and Zen, are emphasized. Part two, profusely illustrated with over 600 clear black and white photographs and 20 line drawings, outlines instruction for kumite (sparring drills). Included are two-person drills such as the double-line drill and the circle drill, which give practice in facing multiple opponents. Descriptions of many of these drills are not found in other English-language books. In addition, nine kata (forms) are presented, two of which, sochin and nijushiho, are rarely seen in print in English. The two parts of this exhaustive book-the first historical and philosophical, the second practical-combine to form one of the most comprehensive presentations of Shotokan karate available in English. Complete Shotokan karate is an essential resource for all those interested in Japanese karate